Epoxidation of Palm Olein as Base Oil for Calcium Complex Bio Grease - Erliza Hambali; Ni Nyoman Indah Adi Puspita (International Journal of Oil Palm, 2021)
The development of palm oil bio grease aimed to substitute grease made from petroleum with a material that is more environmentally friendly. The enhancement of bio grease characteristics can be performed by chemical synthesis. This research aimed to obtain best mole ratio of palm olein and H2O2 in the epoxidation process, and to analyze the physical characteristics of the bio grease products. This process used acetic acid and H2O2 with mole ratio variations of olein and H2O2 of 1: 3, 1: 6, and 1: 9. The mole ratio was selected based on the analysis of iodine and oxiran numbers, which was then processed into bio grease with the addition of calcium stearate and calcium acetate. Epoxidized olein with a mole ratio of olein and H2O2 of 1: 9 was selected because it achieved the highest average oxiran number (0.99), the lowest iodine number (33.09), and it was based on ANOVA and LSD tests. The higher the oxiran number, the more epoxide compounds produced. Low iodine number indicated low unsaturation in fatty acids. The peroxy acid used in the epoxidation process reacted with unsaturated compounds, so that the lower iodine number in the epoxidized olein produced more epoxide compounds. Bio grease had a light cream color, density of 0.96 g/cm3, viscosity of 31,280 mPa.s, unworked penetration of 438 (0.1 mm), worked penetration of 443 (0.1 mm), dropping point < 26°C, corrosion resistance of 2c and NLGI number 00.